Uniform arrays of gold nanoelectrodes with tuneable recess depth - Gordeeva, Elena O.; Roslyakov, Ilya V.; Leontiev, Alexey P.; Klimenko, Alexey A.; Napolskii, Kirill S. (Beilstein Journal of Nanotechnology, 2021)
Nanoelectrode arrays are much in demand in electroanalytical chemistry, electrocatalysis, and bioelectrochemistry. One of the promising approaches for the preparation of such systems is templated electrodeposition. In the present study, porous anodic alumina templates are used to prepare Au nanoelectrode arrays. Multistage electrodeposition is proposed for the formation of recessed electrodes with the ability to tune the distance between the surface of the porous template and the top surface of the nanoelectrodes. A set of complementary techniques, including chronoamperometry, coulometry, and scanning electron microscopy, are used to characterize the nanoelectrode arrays. The number of active nanoelectrodes is experimentally measured. The pathways to further improve the recessed nanoelectrode arrays based on anodic alumina templates are discussed.
Keywords: anodic alumina; gold; nanoelectrode array; recessed electrode; templated electrodeposition

(untitled) - Henstridge, M. C.; Compton, R. G. (Chem. Rec., 2012)

(untitled) - Karimian, N.; Ugo, P. (Curr. Opin. Electrochem., 2019)

(untitled) - Arrigan, D. W. M. (Analyst, 2004)

(untitled) - LaFratta, C. N.; Walt, D. R. (Chem. Rev., 2008)

(untitled) - Zaino, L. P., III; Ma, C.; Bohn, P. W. (Microchim. Acta, 2016)

(untitled) - Menon, V. P.; Martin, C. R. (Anal. Chem. (Washington, DC, U. S.), 1995)

(untitled) - Abbott, J.; Ye, T.; Krenek, K.; Gertner, R. S.; Ban, S.; Kim, Y.; Qin, L.; Wu, W.; Park, H.; Ham, D. (Nat. Biomed. Eng., 2020)

(untitled) - Kim, D.-S.; Kang, E.-S.; Baek, S.; Choo, S.-S.; Chung, Y.-H.; Lee, D.; Min, J.; Kim, T.-H. (Sci. Rep., 2018)

(untitled) - Evans, U.; Colavita, P. E.; Doescher, M. S.; Schiza, M.; Myrick, M. L. (Nano Lett., 2002)

(untitled) - Haschke, S.; Pankin, D.; Mikhailovskii, V.; Barr, M. K. S.; Both-Engel, A.; Manshina, A.; Bachmann, J. (Beilstein J. Nanotechnol., 2019)

(untitled) - Zhang, Y.; Zhou, Q.; Zhao, W.; Chu, W.; Zheng, J. (Electrochim. Acta, 2016)

(untitled) - Ueno, K.; Hayashida, M.; Ye, J.-Y.; Misawa, H. (Electrochem. Commun., 2005)

(untitled) - Al-Zubeidi, A.; Hoener, B. S.; Collins, S. S. E.; Wang, W.; Kirchner, S. R.; Hosseini Jebeli, S. A.; Joplin, A.; Chang, W.-S.; Link, S.; Landes, C. F. (Nano Lett., 2019)

(untitled) - Atighilorestani, M.; Brolo, A. G. (Anal. Chem. (Washington, DC, U. S.), 2017)

(untitled) - Escalera-López, D.; Griffin, R.; Isaacs, M.; Wilson, K.; Palmer, R. E.; Rees, N. V. (Appl. Mater. Today, 2018)

(untitled) - Karyakin, A. A.; Puganova, E. A.; Budashov, I. A.; Kurochkin, I. N.; Karyakina, E. E.; Levchenko, V. A.; Matveyenko, V. N.; Varfolomeyev, S. D. (Anal. Chem. (Washington, DC, U. S.), 2004)

(untitled) - Yang, M.; Qu, F.; Lu, Y.; He, Y.; Shen, G.; Yu, R. (Biomaterials, 2006)

(untitled) - Habtamu, H. B.; Not, T.; De Leo, L.; Longo, S.; Moretto, L. M.; Ugo, P. (Sensors, 2019)

(untitled) - Gaetani, C.; Gheno, G.; Borroni, M.; De Wael, K.; Moretto, L. M.; Ugo, P. (Electrochim. Acta, 2019)

(untitled) - Qin, X.; Li, Z.-Q.; Zhou, Y.; Pan, J.-B.; Li, J.; Wang, K.; Xu, J.-J.; Xia, X.-H. (Anal. Chem. (Washington, DC, U. S.), 2020)

(untitled) - Sabarirajan, D. C.; George, T. Y.; Vlahakis, J.; White, R. D.; Zenyuk, I. V. (J. Electrochem. Soc., 2019)

(untitled) - Bograchev, D. A.; Volgin, V. M.; Davydov, A. D. (Electrochim. Acta, 2013)

(untitled) - Inguanta, R.; Piazza, S.; Sunseri, C. (Electrochim. Acta, 2008)

(untitled) - Napolskii, K. S.; Roslyakov, I. V.; Eliseev, A. A.; Petukhov, D. I.; Lukashin, A. V.; Chen, S.-F.; Liu, C.-P.; Tsirlina, G. A. (Electrochim. Acta, 2011)

(untitled) - Goncharova, A. S.; Napolskii, K. S.; Skryabina, O. V.; Stolyarov, V. S.; Levin, E. E.; Egorov, S. V.; Eliseev, A. A.; Kasumov, Y. A.; Ryazanov, V. V.; Tsirlina, G. A. (Phys. Chem. Chem. Phys., 2020)

(untitled) - Vorobjova, A. I.; Shimanovich, D. L.; Yanushkevich, K. I.; Prischepa, S. L.; Outkina, E. A. (Beilstein J. Nanotechnol., 2016)

(untitled) - Noyan, A. A.; Leontiev, A. P.; Yakovlev, M. V.; Roslyakov, I. V.; Tsirlina, G. A.; Napolskii, K. S. (Electrochim. Acta, 2017)

(untitled) - Petukhov, D. I.; Buldakov, D. A.; Tishkin, A. A.; Lukashin, A. V.; Eliseev, A. A. (Beilstein J. Nanotechnol., 2017)

(untitled) - Roslyakov, I. V.; Shirin, N. A.; Berekchiian, M. V.; Shatalova, T. B.; Garshev, A. V.; Napolskii, K. S. (Microporous Mesoporous Mater., 2020)

(untitled) - Trahey, L.; Becker, C. R.; Stacy, A. M. (Nano Lett., 2007)

(untitled) - Shin, S.; Kong, B. H.; Kim, B. S.; Kim, K. M.; Cho, H. K.; Cho, H. H. (Nanoscale Res. Lett., 2011)

(untitled) - Leontiev, A. P.; Roslyakov, I. V.; Vedeneev, A. S.; Napolskii, K. S. (J. Surf. Invest.: X-Ray, Synchrotron Neutron Tech., 2016)

(untitled) - Feng, Y.; Kim, K.-D.; Nemitz, C. A.; Kim, P.; Pfadler, T.; Gerigk, M.; Polarz, S.; Dorman, J. A.; Weickert, J.; Schmidt-Mende, L. (J. Electrochem. Soc., 2016)

(untitled) - Leontiev, A. P.; Volkova, O. Y.; Kolmychek, I. A.; Venets, A. V.; Pomozov, A. R.; Stolyarov, V. S.; Murzina, T. V.; Napolskii, K. S. (Nanomaterials, 2019)

(untitled) - García-Jareño, J. J.; Navarro-Laboulais, J.; Vicente, F. (Electrochim. Acta, 1996)

(untitled) - Sitnikova, N. A.; Borisova, A. V.; Komkova, M. A.; Karyakin, A. A. (Anal. Chem. (Washington, DC, U. S.), 2011)

(untitled) - Doescher, M. S.; Evans, U.; Colavita, P. E.; Miney, P. G.; Myrick, M. L. (Electrochem. Solid-State Lett., 2003)

(untitled) - Sadykov, A. I.; Kushnir, S. E.; Roslyakov, I. V.; Baranchikov, A. E.; Napolskii, K. S. (Electrochem. Commun., 2019)

(untitled) - Roslyakov, I. V.; Koshkodaev, D. S.; Lebedev, V. A.; Napolskii, K. S. (J. Surf. Invest.: X-Ray, Synchrotron Neutron Tech., 2019)

(untitled) - Lillo, M.; Losic, D. (J. Membr. Sci., 2009)

Electrolyte for bright copper platting "Ecomet MB-16"

Electrolyte for gold platting "Ecomet 04-ZG"